The effect of institutional factors on public-private partnership success in ports - Panayides, Photis; Parola, Francesco; Lam, Jasmine Siu Lee (My University, 2015)
Port public-private partnerships (PPPs) are considered to be an important emerging mechanism for port development and improvement in port performance especially for developing countries. This paper empirically investigates the effect of institutional factors in the success of port's PPPs; the latter defined as the attractiveness of the PPP project for private bidders and the market competitiveness of the facility. The empirical investigation of a large sample of ports finds that 'regulatory quality', 'market openness', 'ease to start a business' and 'enforcing contracts' are important institutional determinants of port PPP success and may ultimately contribute to port development and economic growth. The results are consistent with and add to the theoretical literature whereas practical implications for port authorities, managers and investors are discussed.
Keywords: Institutional environment; Port; Port development; Privatization; Public-private partnerships